(untitled) (Archives of Mechanics - Test, 2006)
Technological metal forming processes of extrusion, forging and rolling with imposed cyclic torsion or shear deformation have been recently studied in view of their advantages with respect to monotonic loading processes, cf. Bochniak and Korbel [2-4]. The present work is aimed to analyze such process in the case of simple tension or compression of a cylindrical tube with imposed cyclic torsional deformation. The material element response is assumed to be rigid-perfectly plastic or elastic-perfectly plastic. For these models, the analytical solutions can be provided for the steady cyclic responses and the effect of two process parameters, namely the ratio of shear and axial strain rates η and the amplitude of shear strain γm, can be clearly demonstrated. Three different regimes of cyclic response can be visualized in the plane η, γm. The cyclic response of a cylinder under combined axial compression and cyclic torsion is predicted by considering a simplified model of a set of concentric tubes and neglecting their radial stress interaction. The axial force and torsional moment are then specified by averaging the responses of consecutive tubes. The cyclic response diagrams for the cylinder are then generated in terms of axial force and torsional moment related to axial deformation and angle of twist.